Two parallel lines are crossed by a transversal.Horizontal and parallel lines k and l are cut by transversal j. At the intersection of lines k and j, the bottom left angle is 120 degrees. At the intersection of lines l and j, the top left angle is h degrees.
What is the value of h?

h = 60
h = 80
h = 100
h = 120

Answers

Answer 1
Answer:

Answer:

∠h=60º

Step-by-step explanation:

1) Since in a pair of parallel lines ∠α and ∠ h are Consecutive interior angles, their sum is 180º, i.e. they are supplementary angles. (Check the first graph)

\alpha +h =180^(o)\Rightarrow 120^(0)+h =180^0\Rightarrow h=60^0

Answer 2
Answer: Answer: H = 60

Explanation: the parallel line (k) cut by the transversal line (j) forms two angles, one of size 120° and the other h°. These angles must be supplementary (add to 180°) therefore h = 180 -120 = 60°

Related Questions

M-1 = -2—9Plsss helppp!!
Computers R US was selling laptops that had 4GB of memory for $495. You can but additional memory for $97 per GB. If your grandfather gave you $980 to buy a laptop and additional memory, how much memory can u get
Factor by grouping:4-12r+9r^2i know the answer is (2-3r)^2Can anyone explain to me how it is?
If point A is between B and C then BA + AC = BC. always sometimes never
Which function has the same why intercept as the graph below

Find the quadratic function y = a(x-h)^2whose graph passes through the given points (6, -1) and (4, 0). a) y = 1/4(x-5)^2 b) y = 1/4(x-5)^2 c) y = -1/4(x-6)^2 d) y = 1/4(x-6)^2

Answers

Answer: -1/2x - 2.

Step-by-step explanation:

To find the quadratic function y = a(x-h) that passes through the points (6, -1) and (4, 0), we can substitute the given points into the equation and solve for a and h. Let's go through the steps:

1. Substitute the coordinates of the first point (6, -1) into the equation:

-1 = a(6 - h)

2. Substitute the coordinates of the second point (4, 0) into the equation:

0 = a(4 - h)

3. Now we have a system of two equations with two unknowns. We can solve this system to find the values of a and h.

From the equation -1 = a(6 - h), we can rewrite it as:

-a(6 - h) = 1

From the equation 0 = a(4 - h), we can rewrite it as:

-a(4 - h) = 0

4. Simplifying the equations, we get:

-6a + ah = 1 (equation 1)

-4a + ah = 0 (equation 2)

5. Subtracting equation 2 from equation 1 eliminates the ah term:

-6a + ah - (-4a + ah) = 1 - 0

-6a + ah + 4a - ah = 1

-2a = 1

6. Solving for a, we divide both sides by -2:

a = -1/2

7. Substitute the value of a back into either equation (let's use equation 2) to solve for h:

-4(-1/2) + h(-1/2) = 0

2 + h/2 = 0

h/2 = -2

h = -4

8. Now we have the values of a = -1/2 and h = -4. We can substitute these values back into the original equation y = a(x-h) to find the quadratic function:

y = -1/2(x - (-4))

y = -1/2(x + 4)

y = -1/2x - 2

Therefore, the quadratic function that passes through the points (6, -1) and (4, 0) is

AI-generated answer

To find the quadratic function y = a(x-h) that passes through the points (6, -1) and (4, 0), we can substitute the given points into the equation and solve for a and h. Let's go through the steps:

1. Substitute the coordinates of the first point (6, -1) into the equation:

-1 = a(6 - h)

2. Substitute the coordinates of the second point (4, 0) into the equation:

0 = a(4 - h)

3. Now we have a system of two equations with two unknowns. We can solve this system to find the values of a and h.

From the equation -1 = a(6 - h), we can rewrite it as:

-a(6 - h) = 1

From the equation 0 = a(4 - h), we can rewrite it as:

-a(4 - h) = 0

4. Simplifying the equations, we get:

-6a + ah = 1 (equation 1)

-4a + ah = 0 (equation 2)

5. Subtracting equation 2 from equation 1 eliminates the ah term:

-6a + ah - (-4a + ah) = 1 - 0

-6a + ah + 4a - ah = 1

-2a = 1

6. Solving for a, we divide both sides by -2:

a = -1/2

7. Substitute the value of a back into either equation (let's use equation 2) to solve for h:

-4(-1/2) + h(-1/2) = 0

2 + h/2 = 0

h/2 = -2

h = -4

8. Now we have the values of a = -1/2 and h = -4. We can substitute these values back into the original equation y = a(x-h) to find the quadratic function:

y = -1/2(x - (-4))

y = -1/2(x + 4)

y = -1/2x - 2

Therefore, the quadratic function that passes through the points (6, -1) and (4, 0) is y = -1/2x - 2.

Joan bought a soft drink for 6.50 dollars and 12 candy bars. She spent a total of 65 dollars. How much did each candy bar cost? Which equation matches this problem?

Answers

Answer:

0.406 (3 d.p)

Step-by-step explanation:

Let's call the cost of each candy bar "x" dollars. We can set up an equation to represent the situation:

6.50 + 12x = 65

This equation represents the problem. Now, we can solve for "x" to find the cost of each candy bar.

6.50 + 12x = 65

12x = 65 - 6.50

12x = 58.50

x = 58.50/12

x = 0.406 (3 d.p)

d.p means decimal point

Mark me brainliest

If the equation of a line has an undefined slope and passes through the point (1, 3), which form would be used to write the equation of the line

Answers

Another version you can use is slope-intercept form.   The two above are standard and point-slope forms. First you do need to find the slope of the line based on m=(y2-y1)/(x2-x1) so for these points: (0,3) and (2,0) --> (x1, y1) and (x2, y2)x1=0y1=3x2=2y2=0 m= (0-3)/(2-0) = -3/2 Then your formula will need to look like y=mx+b where b is your y-intercept (when x=0)  Due to have the x=0 point, you are pretty much done: y=-3/2*x+3 If you do not have a (0,y) form, you can solve as follows:Write out the formula with your slope value inserted:y=-3/2*x+b Choose one of your points on your line to solve for b.  I choose (2,0):0=-3/2*2+b0=-3*1+b3=b --> b=3 

Hi Freedom;(0,3) (2,0)Slope is change-of-y divided by change-of-x...m=(y-y1)/(x-x1)m=(3-0)/(0-2)m=3/-2=-3/2Slope-intercept format is...y=mx+bm is the slope.b is the y-intercept, the value of y when x=0.y=(-3/2)x+bThe y intercept is provided as (0,3)...y=(-3/2)x+3 

(0,3) & (2,0) are the y and x intercepts, so the intercept form is x/2 + y/3 = 1. Multiply both sides by 6: 3x + 2y = 6. 

The slope of the line,m=y-y1/x-x1                             m=3-0/0-2=-3/2 The point slope form is y-y1=m(x-x1) y-0=-3/2(x-2) y=-3/2(x-2) 2y=-3x+6 3x+2y=6 

hope this helps hope i am brainliest 

For which function is the ordered pair (4, 12) not a solution?y = 3x
y = x + 8
y = 16 - x
y = 8 - x

Answers

It's D since 8 - 4 = 4, not 12.

Answer:

Y=8-x

So the answer is in fact D.

Issa jogged 2/3 of the way home from school .Then he was tired ,so he walked the remaining 3,200 m how many kilometers did he travel from school to home

Answers

Answer:

9.6 km

Step-by-step explanation:

Issa jogged 2/3 of the way home from school.

Then he was tired, so he walked the remaining 3200 m.

In other words, the remaining 3200 m is 1/3 of the way from school to home.

Let the distance from school to home be x. Therefore:

(1)/(3)  * x = 3200\n\n=> x = 3200 * 3 \n\nx = 9600 m

Therefore, from school to home he traveled 9600 m.

To put this is kilometres:

1000 m = 1 km

9600 m = 9600 / 1000 = 9.6 km

He traveled 9.6 km from school to home.

The diameter of a circle has endpoints whose coordinates are R(-2, 2) and S(4, 2). what is the length of the radius?

Answers

Answer: 3 units

Step-by-step explanation:

Using distance formula :

√((x_2-x_1)^2+(y_2-y_1)^2)

The diameter of the circle with endpoints  R(-2, 2) and S(4, 2) will be

d=√((4+2)^2+(2-2)^2)=√(36)=6\ units

Since, the radius of a circle is half of the diameter.

Then the radius of the circle will be

r=(d)/(2)=(6)/(2)=3\ units

Hence, the radius of the circle = 3 units.

Answer:

the answer is 3

Step-by-step explanation: